Analisis Implementasi Electronical Digital Information System (E-Digis) Dalam Proses Manajemen Data Dinas Kesehatan Kota Pasuruan - Rizqiyatul Khoiriyah (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
Implementing the Health Information System (SIK) in managing information technology-based data and information using the E-Digis (Electronic Digital Information System) application is a breakthrough made by the Pasuruan City Health Office in public services to realize good data and information management. The purpose of this research is to find out whether the implementation of the Electronic Digital Information System (e-Digis) in managing data and information at the Pasuruan City Health Office has been run by the provisions in data and information management. In addition, to identify obstacles and obstacles to implementation so that opportunities for improving the performance of the Electronic Digital Information System (e-Digis) can be identified. The method used in this study is a qualitative descriptive method. The results showed that there was already a conformity of e-Digis with the processes running in data and information management at the Pasuruan City Health Office. However, there were shortcomings in its implementation such as supporting infrastructure and system user training.